The Universal Light, or the Only Way to the Father? Universalism and Exclusivism in John’s Provocative Christology - Paul N. Anderson (Religions, 2024)
Among the most perplexing of John’s theological riddles is question of salvific universalism and particularity. John is both the greatest biblical source of Christian universalism and the greatest source of Christian exclusivity. After all, the Johannine Overture affirms universal access to the saving–revealing Light of Christ, declaring: “The true light, which enlightens everyone, was coming into the world!” (Jn 1:9). What else could this mean, other than to affirm that every person has saving access to the divine Light of Christ? And yet, Jesus also declares in John 14:6, “I am the way, and the truth, and the life. No one comes to the Father except through me!” What could this mean, other than to assert that there is only one means of access to God, and that it involves saving belief in Jesus as the Christ? Sorting out the apparent contradictions within these tensions is the goal of the present essay.